Mortality reduction from gastric cancer by endoscopic and radiographic screening - Hamashima, Chisato; Shabana, Michiko; Okada, Katsuo; Okamoto, Mikizo; Osaki, Yoneatsu (Cancer science, 2015)
To evaluate mortality reduction from gastric cancer by endoscopic screening, we undertook a population‐based cohort study in which both radiographic and endoscopic screenings for gastric cancer have been carried out. The subjects were selected from the participants of gastric cancer screening in two cities in Japan, Tottori and Yonago, from 2007 to 2008. The subjects were defined as participants aged 40–79 years who had no gastric cancer screening in the previous year. Follow‐up of mortality was continued from the date of the first screening to the date of death or up to December 31, 2013. A Cox proportional hazards model was used to estimate the relative risk (RR) of gastric cancer incidence, gastric cancer death, all cancer deaths except gastric cancer death, and all‐causes death except gastric cancer death. The number of subjects selected for endoscopic screening was 9950 and that for radiographic screening was 4324. The subjects screened by endoscopy showed a 67% reduction of gastric cancer compared with the subjects screened by radiography (adjusted RR by sex, age group, and resident city = 0.327; 95% confidence interval [CI], 0.118–0.908). The adjusted RR of endoscopic screening was 0.968 (95%CI, 0.675–1.387) for all cancer deaths except gastric cancer death, and 0.929 (95%CI, 0.740–1.168) for all‐causes death except gastric cancer death. This study indicates that endoscopic screening can reduce gastric cancer mortality by 67% compared with radiographic screening. This is consistent with previous studies showing that endoscopic screening reduces gastric cancer mortality. This study indicates that endoscopic screening can reduce gastric cancer mortality by 67% compared with radiographic screening. This is consistent with previous studies showing that endoscopic screening reduces gastric cancer mortality.